2017
DOI: 10.1016/j.nut.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and efficacy of a polyamine-deficient diet for the treatment of perioperative pain

Abstract: Suppression of polyamines from the diet offers a nutrition-based treatment option for perioperative pain reduction independent of and complementary to typical analgesic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Polyamines are found in foods such as broccoli, cauliflower and citrus fruits. A recent study showed a polyamine‐deficient diet resulted in a rapid reduction of high intensity pain in acute pain . In addition, subcutaneous injections of spermidine or spermine triggered mechanical allodynia and oedema (rat model) .…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Polyamines are found in foods such as broccoli, cauliflower and citrus fruits. A recent study showed a polyamine‐deficient diet resulted in a rapid reduction of high intensity pain in acute pain . In addition, subcutaneous injections of spermidine or spermine triggered mechanical allodynia and oedema (rat model) .…”
Section: Natural Compoundsmentioning
confidence: 99%